DEVELOPMENT OF PHOTOCATALYTIC AND ULTRASONIC EQUIPMENT TO PREVENT THE SPREAD OF CORONAVIRUS SARS-COV-2. EXPERIMENTAL SAMPLE OF SEPARATION STAGES - Huang , Chun Xiang; Liling , Xia; Ryzhkov , Sergiy (Управління розвитком складних систем, 2021)
The aim of the work is to develop experimental sample of separation elements for photocatalytic and ultrasonic equipment for air purification for infectious safety of buildings from coronavirus SARS-COV-2. During the research and development work on creation of Experimental sample of air filter of separation stages for photocatalytic and ultrasonic equipment for air purification for infectious safety of buildings from coronavirus SARS-COV-2 using turboimpact separation technologies, a working 3 dimensional model of geometry was created. 3D printing technologies were used to create Plastic model of experimental Sample. 3D model for 3D printer was created. The Full-scale metal experimental sample of Air Filter for air purification and oil and dust separation consists of 3 equal Purification modules. Each of the modules consists of 3 stages for experiments and increasing of purification level. The equipment is designed for air volume G = 50… 150 m3/hour, should reduce the degree of microbial contamination of the air to the required level (capture particles of 0.1 μm) and help reduce the risk of airborne diseases. Project considers solving an important scientific and technical problem of creating and development of photocatalytic and ultrasonic heat and mass transfer separation equipment for air clean from dust and viruses (coronavirus SARS-COV-2).